Tinjauan Literatur Sistematis Pendekatan STEM dan STEAM dalam Pendidikan Vokasi - Laksono, Ahmad Triyo; Kuncahyono, Kuncahyono (Journal Of Education And Teaching Learning (JETL), 2026)
The accelerating transformation toward Industry 4.0 and the emerging paradigm of Industry 5.0 have fundamentally reshaped vocational education by demanding new forms of competence that integrate technical expertise, creativity, and adaptive innovation. This study explores how the integration of STEM (Science, Technology, Engineering, and Mathematics) and STEAM (Science, Technology, Engineering, Arts, and Mathematics) pedagogical frameworks, supported by Project-Based Learning (PjBL), can address these evolving educational demands. Using a Systematic Literature Review (SLR) methodology, this research synthesizes findings from international and regional studies published between 2015 and 2025 to examine the alignment of STEM/STEAM-PjBL with vocational education reform. The review identifies key trends in teacher readiness, digital pedagogy, curriculum innovation, and competency outcomes. Findings reveal that STEM enhances analytical reasoning and technical proficiency, while STEAM expands learning by incorporating creativity, design thinking, and aesthetic awareness attributes crucial for human-centered innovation. PjBL emerges as the pedagogical bridge connecting theoretical knowledge with industrial practice, fostering critical thinking, collaboration, and problem-solving skills. However, the review also highlights challenges such as limited teacher training, insufficient infrastructure, and fragmented institutional support that hinder implementation. The study concludes that integrating STEM/STEAM through PjBL represents a comprehensive educational paradigm capable of producing vocational graduates who are not only technically proficient but also innovative, digitally literate, and adaptable to the rapidly evolving global industry landscape. These insights contribute to future-oriented policy and pedagogical reform, positioning STEM/STEAM-PjBL as a transformative model for sustainable vocational education.